J. M. Keynes, The General Theory and George Boole: Keynes’s Uncertainty is based on Boolean Uncertainty as analyzed in The Laws of Thought - BRADY, Michael Emmett (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).07, 2025)
This paper contributes to the literature on Keynes by showing that Keynes’s understanding and analysis of the role of uncertainty in decision making originated from his reading of George Boole’s The Laws of Thought . Boole’s The Laws of Thought was the first mathematically and logically advanced treatise(Thomas Aquinas and Adam Smith had both recognized that real world decision making could not be based on the purely mathematical laws of the probability calculus) on uncertainty, demonstrating that the purely mathematical laws of the probability calculus, based on additivity and linearity were, at best, only a limiting, special  case that would rarely occur in the real world of decision making which were characterized by non-additivity and non-linearity. Keynes then developed the basic foundational analysis of Boole further in his A Treatise on Probability and General Theory .Keynes advanced Boole’s theory by developing his own version of Boole’s logical, objective, probability relation, theory of groups, upper-lower, interval bounded imprecise probabilities, as well as the evidential weight of the argument, which would allow a treatment of uncertainty in the form of a decision weight approach instead of by interval estimates. Keynes called this approach his conventional coefficient of weight and risk, c, in Chapter XXVI of the A Treatise on Probability .